2017
DOI: 10.1002/bio.3328
|View full text |Cite
|
Sign up to set email alerts
|

Interaction studies of copper complex containing food additive carmoisine dye with human serum albumin (HSA): Spectroscopic investigations

Abstract: In this study, the interaction between human serum albumin (HSA) and a copper complex of carmoisine dye; [Cu(carmoisine) (H O) ], was studied in vitro using multi-spectroscopic methods. It was found that the intrinsic fluorescence of HSA was quenched by the addition of the [Cu(carmoisine) (H O) ] complex and the quenching mechanism was considered as static quenching by formation of a [Cu(carmoisine) (H O) ]-HSA complex. The binding constant was about 10 M at room temperature. The values of the calculated therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…The values of ∆ H , ∆ S , and ∆ G for the interaction between 4MMC and BSA were listed in Table . From the table, the negative value of ∆ H and the positive value of ∆ S indicate that the formation of 4MMC‐BSA complex is driven by exothermic process, which involves the hydrophobic interaction with hydrogen bonding, playing a major role in the 4MMC‐BSA binding interaction . Further, the negative value of ∆G suggested that the interaction process is spontaneous.…”
Section: Resultsmentioning
confidence: 97%
“…The values of ∆ H , ∆ S , and ∆ G for the interaction between 4MMC and BSA were listed in Table . From the table, the negative value of ∆ H and the positive value of ∆ S indicate that the formation of 4MMC‐BSA complex is driven by exothermic process, which involves the hydrophobic interaction with hydrogen bonding, playing a major role in the 4MMC‐BSA binding interaction . Further, the negative value of ∆G suggested that the interaction process is spontaneous.…”
Section: Resultsmentioning
confidence: 97%
“…CD technique is employed for studying the secondary structure of polypeptides and proteins in biological chemistry [43] . Commonly, far UV‐vis CD spectra (from 200 nm to 260 nm) reveal the secondary structure of the albumin protein [44] .…”
Section: Resultsmentioning
confidence: 99%
“…Commonly, far UV‐vis CD spectra (from 200 nm to 260 nm) reveal the secondary structure of the albumin protein [44] . The advent of two negative signals at 208 and 222 nm is the characteristic of the albumin α‐helical form, which is caused by charge transition (n→π*) in the covalent peptide bond of the α‐helix structure [43] . The serum protein CD spectra were taken before and after interacting with the zinc(II) complex to investigate the alterations in the secondary form of HSA and to acquire more specific information regarding it [45] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estos últimos se continúan usando dado que poseen tres características muy interesantes: producción muy barata, tinte muy fuerte y una buena estabilidad química (Downham y Collins, 2000;Oreopoulou et al, 2009). No obstante, los colorantes sintéticos, si bien son muy versátiles en la industria alimentaria se han hallado en varios estudios que presentan una correlación positiva entre el consumo de los mismos y diversas alteraciones en la salud como: la hiperactividad (Bateman et al, 2004;McCann et al, 2007;Oplatowska-Stachowiak y Elliott, 2015), los defectos en el ADN (Khan et al, 2020), las reacciones alérgicas dermatológicas (Bateman et al, 2004;Panachiyil et al, 2019), la interacción con proteínas (Basu Y Suresh Kumar, 2015; Shahabadi et al, 2017;Wang et al, 2019) (Wopara et al, 2021).…”
Section: Introductionunclassified